Advances in Structural Health Monitoring - Hassan, Maguid H.M (IntechOpen, 2019)
The concepts presented in this book are some of the new advancements in the design of structural health monitoring systems. It is envisaged that such advancements will lead to smart structural health monitoring that will result in sustainable engineering systems. Sustainability is considered an important objective in today's engineering design due to the current state of climate change and global warming, both of which are hugely aggravated by industrial and construction activities. This book presents demonstrations of and applications for new advancements such as infrared thermography, ultrasonic guided waves, and strain sensors, among others. The information presented will encourage further research and implementation of these advanced techniques and technologies in structural health monitoring.